Kehidupan Sosial Ekonomi Petani Penggarap Di Kenagarian Koto Baru Kecamatan X Koto Kabupaten Tanah Datar Tahun 2000- 2020 - Amir Syarifudin; Najmi Najmi (Jurnal Kronologi, 2023)
This research discusses the socio-economic life of sharecroppers in the Koto Baru district, X Koto district, Tanah Datar district in 2000-2020. The research problems are formulated as follows: (1) What is the background of the emergence of sharecroppers in Kenaganan Koto Baru (2) How do sharecroppers get arable land in Kenaganan Koto Baru. (3) How is the social and economic life of sharecroppers in Kenagarian Koto Baru? This writing aims to explain the socio-economic life of sharecroppers in Kenaganan Koto Baru, X Koto district, Tanah Datar district. as the guardian of the Koto Baru village, to open their agricultural land, they were financed and given pocket money to work on the land. Cultivator farmers obtain arable land in three ways, namely by renting, by means of profit sharing, and or by becoming laborers or daily wages. Socio-economic life of sharecroppers in New Koto State.